Notas de una investigación: migración, clandestinidad y puesta en juego de la identidad.: Acercamiento a las problemáticas de migración e identidad para una lectura de Io, venditore di elefanti (1990) de Pap Khouma (El Hilo de la Fabula, 2019)
The present work arises as a partial result of an adscription project in research carried out in the French and Italian Literatures Chair (FHUC–UNL). Our purpose as regards this is to focus on the migratory journey as an object of study that can account for the inadequacy of the concept of «national» in the field of literature. First we will postulate a theoretical framework in which we will realize the need to think about cultural identity in relation to literature  nd position ourselves from the field of comparative studies to understand migration as a phenomenon that allows us to question the relationships established in the literary field. Later we will expose part of the contributions that we use to think about the journey story as an enabler of new identity issues proposed for the reading of Khouma’s novel.
Keywords: Pap Khouma; Migration; Identity